Unity and Multiplicity : the road to Openness. Plotinus in Henri Bergson’s Thought - Costa Carvalho, Magda (2021)
Looking for the influence of the Plotinian thought on Henri Bergson’s philosophy is not an easy task to fulfil. I’ve been devoted to it for two or three times in the last few years and each time I try to think about the subject I end up with what seems to be another piece of the puzzle. This would obviously be a good thing if I didn’t also end up with different ideas about the whole picture represented in that puzzle. Mainly for this reason, my paper didn’t end up being what it was initially planned to be. And because the presence of Plotinus in Bergson’s work is a subject to which I can’t find a linear answer, my title is now more of a future path to cross, than a present reality.